2016
DOI: 10.1016/j.cej.2015.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of gas–solids flow in a bubbling fluidized bed with immersed vertical U-tube banks

Abstract: We apply a two-fluid model (TFM) from the open-source code Multiphase Flow with Interphase eXchanges (MFIX) to investigate hydrodynamics in a gas-solids fluidized bed with immersed vertical tubes. The cut-cell method implemented in MFIX is used to fully resolve the flow around vertical U-tube banks. Simulations are performed in a bed diameter of 0.145 m with square and triangular tube arrangements, for inlet gas velocities of U 0 /U mf = 2.3, 4.5 and 6.8. Simulation results are compared with experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Further, the framework developed in this study can be used to derive similar non-dimensional relations for other practical systems e.g. fluidized beds with internals [56,57] where the choice of horizontal and vertical spacings significantly affect bubble dynamics and are likely to be crucial for scalability (instead of D and H 0 ). Nevertheless, this study demonstrates the importance of geometric parameters while considering scale-up (or scale-down) of fluidized beds.…”
Section: Scale-up Considerationsmentioning
confidence: 97%
“…Further, the framework developed in this study can be used to derive similar non-dimensional relations for other practical systems e.g. fluidized beds with internals [56,57] where the choice of horizontal and vertical spacings significantly affect bubble dynamics and are likely to be crucial for scalability (instead of D and H 0 ). Nevertheless, this study demonstrates the importance of geometric parameters while considering scale-up (or scale-down) of fluidized beds.…”
Section: Scale-up Considerationsmentioning
confidence: 97%
“…Numerical simulation is a powerful tool for modeling gas-solid motion. Various models have been used to predict the performance of fluidized systems of different scales Xu et al, 2017a, Verma et al 2016. Among those models, CFD-DEM, where particle motion, collisional forces and gas-particle interactions are included, has been demonstrated to be able to capture key flow features such as bubbles and clusters.…”
Section: Coarse-grain Demmentioning
confidence: 99%
“…In order to account for the particle streaming and collisional contributions, a set of constitutive relations need to be included on the model. These relations are additional closure sub-models, which account for phenomena such as the granular viscosity, granular bulk viscosity, frictional viscosity, frictional pressure, and granular temperature [34][35][36]. In this sense, despite that it has been observed that the KTGF approach can provide good qualitative and quantitative predictions, it should be noted that it is required to make a proper selection of vast coupled sub-models, which should be based on the underlying assumptions for their derivation and their range of applicability.…”
Section: Introductionmentioning
confidence: 99%